Studies on Sono-Chemical Biodiesel Production Using Smoke Deposited Nano MgO Catalyst - P. Sivakumar; S. Sankaranarayanan; S. Renganathan; P. Sivakumar (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
The comprehensive study of smoke deposited nano sized MgO as a catalyst for biodiesel production was investigated. The transesterification reaction was studied under constant ultrasonic mixing for different parameters like catalyst quantity, methanol oil molar ratio, reaction temperature and reaction time. An excellent result of conversion was obtained at 1.5 wt% catalyst; 5:1 methanol oil molar ratio at 55°C, a conversion of 98.7% was achieved after 45 min. The conversion was three to five times higher than those are reported for laboratory MgO in literature. This was mainly due to the enhancement of surface area of the catalyst and the activity of ultrasonic waves. Catalyst is easily recovered and reused up to eight times with easy regeneration steps. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)